2022
DOI: 10.1021/acsbiomaterials.1c01502
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Decellularized Natural Cellulose Scaffolds with Organosilanes for Bone Tissue Regeneration

Abstract: The utility of plant tissues as scaffolding materials has been gaining significant interest in recent years owing to their unique material characteristics that are ideal for tissue regeneration. In this study, the degradation and biocompatibility of natural cellulosic scaffolds derived from Borassus f labellifer (Linn.) (BF) immature endosperm was improved by chemical oxidation and surface functionalization processes. Briefly, thus obtained cellulosic scaffolds were sequentially processed via a detergent excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…It is obvious from the studies that the collagen and noncollagen protein-derived peptides guide the phenotypic switch to M2 macrophages and augment the secretion of anti-inflammatory factors. The in vitro osteogenic differentiation potential of scaffolds is equivalent to self-assembled peptide gels, polymeric and peptide-modified polymer derivatives, hybrid biopolymers, and nanoparticles reported in the literature by Alshehri et al, Mahendiran et al, Tang et al, and Gilarska et al…”
Section: Resultsmentioning
confidence: 75%
“…It is obvious from the studies that the collagen and noncollagen protein-derived peptides guide the phenotypic switch to M2 macrophages and augment the secretion of anti-inflammatory factors. The in vitro osteogenic differentiation potential of scaffolds is equivalent to self-assembled peptide gels, polymeric and peptide-modified polymer derivatives, hybrid biopolymers, and nanoparticles reported in the literature by Alshehri et al, Mahendiran et al, Tang et al, and Gilarska et al…”
Section: Resultsmentioning
confidence: 75%
“…In another study, scaffolds based on cellulose were modified by sodium periodate oxidation and amino-terminated 3-aminopropyltriethoxysilane and methyl-terminated octadecyltrichlorosilane. In addition to improvement in the swelling ratio, porosity, surface area, degradation behavior, and mechanical properties of scaffolds, enhanced cell adhesion, proliferation and differentiation of osteoblasts with upregulation of mineralization were observed [215].…”
Section: Surface Chemistry and Compositionmentioning
confidence: 98%
“…Surface modification also has the capacity to facilitate the functionalisation of more unlikely material candidates for this research into more suitable substances. An example of this is offered by Mahendiran et al, who examined the potential of cellulose scaffolds derived from Borassus flabellifer for the purpose of bone tissue regeneration [ 166 ]. The scaffolds were derived from the plant’s immature endosperm which was then, after washing and oxidising the scaffolds, modified by two organosilanes; amino-terminated aminopropyltriethoxysilane (APTES) and methyl-terminated octadecyltrichlorosilane (OTS).…”
Section: Surface Modificationmentioning
confidence: 99%
“…The following supporting information can be downloaded at https://www.mdpi.com/article/10.3390/biomimetics8020205/s1: Table S1: A synopsis of each study described within this article, including the authors and publication year, material and tissue type, and testing and mechanical property information, as well as a brief summary, where appropriate, of each research paper reported thus far [29,64,113,[115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148]152,156,157,[159][160][161][162][163][164][165][166]…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation